EXPLORING THE INFLUENCE OF CONSUMER PERCEPTION AND ATTITUDES ON THE PURCHASE INTENTIONS OF ELECTRIC VEHICLES IN INDIA (CAHIERS MAGELLANES-NS, 2024)
The main objective of this study is to examine consumer opinion and purchasing Intentions regarding electric automobiles in India. In response to environmental challenges, the Indian Government is implementing favorable policies to promote electric car sales, enabling the nation to achieve the UN climate objectives of reducing greenhouse gas emissions. Moreover, India ranks among the largest automotive markets globally, and the electric car sector exhibits significant growth potential. This research employs a quantitative methodology and questionnaires to investigate the problem statement. This research empirically examines the factors influencing consumers' propensity to acquire electric vehicles and their perceptions about electric vehicles in India. It offers insights for electric car producers and the Government regarding consumer expectations for electric vehicles in India.